30 Li+‐Accommodating Covalent Organic Frameworks as Ultralong Cyclable High‐Capacity Li‐Ion Battery Electrodes - Zhai, Lipeng; Li, Gaojie; Yang, Xiubei; Park, Sodam; Han, Diandian; Mi, Liwei; Wang, Yanjie; Li, Zhongping; Lee, Sang‐Young (Advanced functional materials, 2022)
Covalent organic frameworks (COFs) have attracted considerable attention as a facile and versatile design platform for advanced energy storage materials owing to their structural diversity, ordered porous structures, and chemical stability. In this study, a redox‐active COF (TP–OH–COF) that can accommodate 30 Li+ ions is synthesized for potential use as an ultralong cyclable high‐capacity lithium‐ion battery electrode material. The TP–OH–COF is synthesized using triformylpholoroglucinol and 2,5‐diaminohydroquinone dihydrochloride under solvothermal conditions. The accommodation of such exceptional Li+ ion content in the TP–OH–COF is achieved by alternately tethering redox‐active hydroxyl and carbonyl sites on the pore walls. Owing to this unique chemical/structural feature, the TP–OH–COF delivers a high specific capacity of 764.1 mAh g–1, and capacity retention of 63% after 8000 cycles at a fast current density of 5.0 A g–1. A redox‐active COF with alternate tethering of redox‐active hydroxyl and carbonyl sites on the pore walls is demonstrated as an organic‐based, ultralong cyclable high‐capacity LIB anode material. This COF electrode accommodated 30 Li+ ions owing to its unique framework structure and materials chemistry, which has never been reported in previous studies on COF‐based electrode materials.